A bi-objective mixed capacitated arc routing problem based on epsilon constraint algorithm - Miao, Ting-ting; Qin, Tian-bao (SPIE, 2023)
The classified collection of urban waste by waste collection vehicles involves one-way and two-way roads. At the same time, the capacity of collection vehicles is limited. Therefore, the waste sorting and collection problem is modeled as a mixed capacitated arc routing problem (MCARP), hybrid refers to the presence of edge and arc elements, which approximates a real road network and is solved using the Epsilon constraint method. Relative to the existing literature, the model also considers the classified collection of different types of waste and the fairness of the workload of collection workers, and a Bi-objective MCARP model is developed and solved using the Epsilon constraint algorithm method. Finally, a set of cases of different scale is designed to be solved in numerical experiments to determine the solution scale of the model.